Measurement and QCD analysis of double-differential inclusive jet cross sections in proton-proton collisions at √s = 13 TeV - KAYA, MİTHAT (My University, 2022)
© 2022, The Author(s).A measurement of the inclusive jet production in proton-proton collisions at the LHC at s = 13 TeV is presented. The double-differential cross sections are measured as a function of the jet transverse momentum pT and the absolute jet rapidity |y|. The anti-kT clustering algorithm is used with distance parameter of 0.4 (0.7) in a phase space region with jet pT from 97 GeV up to 3.1 TeV and |y| < 2.0. Data collected with the CMS detector are used, corresponding to an integrated luminosity of 36.3 fb−1 (33.5 fb−1). The measurement is used in a comprehensive QCD analysis at next-to-next-to-leading order, which results in significant improvement in the accuracy of the parton distributions in the proton. Simultaneously, the value of the strong coupling constant at the Z boson mass is extracted as αS(mZ) = 0.1170±0.0019. For the first time, these data are used in a standard model effective field theory analysis at next-to-leading order, where parton distributions and the QCD parameters are extracted simultaneously with imposed constraints on the Wilson coefficient c1 of 4-quark contact interactions. [Figure not available: see fulltext.]
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (SCI); FİZİK, NÜKLEER; Natural Sciences (SCI); PHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; Hadron-Hadron Scattering; Jet Physics